2019
DOI: 10.1016/j.jvs.2018.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Geometric analysis of ruptured and nonruptured abdominal aortic aneurysms

Abstract: The geometric analysis performed in this study revealed that ruptured AAAs had a smaller fillet radius and smaller aspect ratio than nonruptured AAAs did.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…This study complements the studies carried out by Jusko et al [ 22 ], Fillinger et al [ 60 ], Di Martino et al [ 61 ], and Kimura et al [ 62 ], who demonstrated that the geometric analysis of the AAA provides valuable information, with a predictive role superior to that of the maximum diameter in the case of the risk of AAA rupture.…”
Section: Discussionsupporting
confidence: 84%
“…This study complements the studies carried out by Jusko et al [ 22 ], Fillinger et al [ 60 ], Di Martino et al [ 61 ], and Kimura et al [ 62 ], who demonstrated that the geometric analysis of the AAA provides valuable information, with a predictive role superior to that of the maximum diameter in the case of the risk of AAA rupture.…”
Section: Discussionsupporting
confidence: 84%
“…The differences in AAA morphology, the length and characteristics of the aortic section it covers, as well as the histological structure of the vascular wall make it reasonable to look for individual factors that would allow the patient to be provided with surgical treatment. There may be factors other than the maximum size of the aneurysm, which, according to the variables mentioned above, could in some cases lower the diameter importance [ 7 , 10 , 25 ]. In the current guidelines, the only manifestations of taking into account the individual characteristics of a certain patient are lowering the AAA size range due to the female gender and qualifying patients for surgical treatment with AAA, which increases its maximum size relatively quickly [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The starting point of this study is the assumption that even a single CT scan can provide more data indicating an increased risk of AAA rupture in a certain patient than the maximal aneurysm size alone. A study by Kimura et al took into account, for example, the fillet radius and the aspect ratio, the parameters whose values, obtained through a single CT scan, distinguished RAAA from AAA [ 25 ]. In our study, emphasis was placed on taking into account the size of the unchanged aorta and iliac arteries and comparing them to the size of aneurysm sac.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…have been confirmed as key factors affecting AAA physiology and pathology [ 9 , 10 ]. Meanwhile, various studies have shown that the gender difference in the risk of AAA rupture might be caused not only by physiological factors (such as LDL and sex hormone) [ 11 13 ] but also by anatomical factors [ 14 ] (such as the body size and the diameter of the aorta [ 15 ]). Therefore, the present study hypothesized that the differences in anatomical structure between female and male would influence the hemodynamics in the AAA which might induce different biological consequences.…”
Section: Introductionmentioning
confidence: 99%